2022
DOI: 10.1093/sp/jxac006
|View full text |Cite
|
Sign up to set email alerts
|

“I Was Facilitating Everybody Else’s Life. And Mine Had Just Ground to a Halt”: The COVID-19 Pandemic and its Impact on Women in the United Kingdom

Abstract: A growing body of research has highlighted the disproportionately negative impact of the COVID-19 pandemic on women globally. This article contributes to this work by interrogating the lived realities of sixty-four women in the United Kingdom through semi-structured in-depth interviews, undertaken during the first and second periods of lockdown associated with COVID-19 in 2020. Categorizing the data by subgroup of women and then by theme, this article explores the normative and policy-imposed constraints exper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Deterioration in mental health has been found to be one of the most prevalent direct and indirect consequences of the COVID-19 virus (Chaturvedi et al 2022;Dotsikas et al 2023). The most important gendered effects on deterioration in mental health in women have been revealed as being related to increased levels of caring responsibilities and domestic duties within the home and increased levels of domestic violence during the COVID-19 pandemic in the UK and across societies globally (Proto and Quintana-Domeque 2021;Xue and McMunn 2021;Herten-Crabb and Wenham 2022;Dotsikas et al 2023;Kourti et al 2023). As in societies globally, the closures of schools and nurseries during the two lockdowns were found to exacerbate these conditions for women.…”
Section: Health Inequalities Arising From the Covid-19 Pandemicmentioning
confidence: 99%
See 2 more Smart Citations
“…Deterioration in mental health has been found to be one of the most prevalent direct and indirect consequences of the COVID-19 virus (Chaturvedi et al 2022;Dotsikas et al 2023). The most important gendered effects on deterioration in mental health in women have been revealed as being related to increased levels of caring responsibilities and domestic duties within the home and increased levels of domestic violence during the COVID-19 pandemic in the UK and across societies globally (Proto and Quintana-Domeque 2021;Xue and McMunn 2021;Herten-Crabb and Wenham 2022;Dotsikas et al 2023;Kourti et al 2023). As in societies globally, the closures of schools and nurseries during the two lockdowns were found to exacerbate these conditions for women.…”
Section: Health Inequalities Arising From the Covid-19 Pandemicmentioning
confidence: 99%
“…A deeper understanding of these impacts requires recognition of existing and deeply embedded social norms, economic inequalities, and unequal power relations (Oreffice and Quintana-Domeque 2021). Recent evidence has informed understandings of the immediate effects of COVID-19 on gender inequality particularly regarding the increased burden of unpaid care work, health, education, and gender-based violence (O'Donnell et al 2021;Flor et al 2022;Herten-Crabb and Wenham 2022;Dotsikas et al 2023). Moreover, recent research has identified gendered themes in caregivers' discourse and reports on patterns among caregivers (Ioanna et al 2021;Dotsikas et al 2023).…”
Section: Background and Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If war demands civilian sacri ce, then a greater demand on the working mother -the need to 'hold it all together' (Herten-Crabb and Wenham, 2022: 1229), as one study participant described it, or transform into a 'superhero' in the words of another (Herten-Crabb and Wenham, 2022: 1226) -is to be expected. Speci cally, many UK women found themselves constantly balancing household tasks with minding the children and helping with schoolwork (Adisa et al, 2021: Herten-Crabb andWenham, 2022). The 'supermum' can thus be thought of as an extension of the 'double burden' of work and care described in feminist literature (Hochschild, 1989), jointly caused by it and COVID lockdowns.…”
Section: 'Supermum'mentioning
confidence: 99%
“…The COVID-19 pandemic context presents both barriers and opportunities for gender-transformative leadership in WASH. On one hand, the highly gendered nature of the pandemic (Simba and Ngcobo, 2020;Wenham et al, 2020;Herten-Crabb and Wenham, 2022) has highlighted how structural inequalities continue to impact women's roles and experiences. On the other, the disruptions brought by the pandemic and responses present opportunities for social innovations that can drive transformative change (Montgomery and Mazzei, 2021).…”
Section: Introductionmentioning
confidence: 99%